2014
DOI: 10.4238/2014.april.17.6
|View full text |Cite
|
Sign up to set email alerts
|

Role of XRCC1 and ERCC5 polymorphisms on clinical outcomes in advanced non-small cell lung cancer

Abstract: ABSTRACT. We aimed to assess the role of polymorphisms of the XRCC1 Arg194Trp, XRCC1 Arg399Gln, ERCC5 His1104Asp, and ERCC5 His46His genes on clinical outcomes of advanced non-small cell lung cancer (NSCLC) patients receiving platinum-based chemotherapy regimens. A total of 378 NSCLC patients were asked to participate within 1 month after diagnosis between January 2005 and January 2006, and they were followed up until November 2011. Genomic DNA of the four genes was extracted using the Qiagen Blood Kit. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…(2014)Asian (China)192132/6060.8 (26–79)IIIA-IVPlatinum-basedOR, OSMALDI-TOF-MS ERCC1 rs3212986 rs11615 rs2298881 105 Lv, H. (2014)Asian (China)9154/3759 (34–80)IIIB-IVDDP+TAX/GEM/NVPORTaqMan-MGB GSTP1 rs1695 106 Krawczyk, P. (2014)Caucasian (Poland)11559/5661 (NR)II-IVDDP/CBP+PEMOSHRM, PCR-RFLP ERCC1 rs11615 107 Sullivan, I. (2014)Caucasian (Spain)161125/3663.7 (36–85)IIIA-IVDDP/CBP-basedOR, OSDynamic array chips ERCC1 rs3212986 rs11615, XPD rs13181 rs1799793, XPG rs1047768 rs17655, XRCC1 rs25487 rs1799782, rs25489, XPA rs1800975 108 Dong, C M. (2014)Asian (China)9238/5457 (40–6)IIIB-IVPlatinum-basedORPCR-RFLP MTHFR rs1801133 109 Liu, D. (2014)Asian (China)378297/8162.4 (36–78)I-IVDDP+GEM/DOC/NVP/TAXOR, OSPCR-RFLP XPG rs1047768 rs17655 XRCC1 rs25487 rs1799782 110 Kou, G. (2014)Asian (China)5014/3656 (45–78)IIIB-IVDDP+NVPORPCR-RFLP ERCC1 rs3212986 111 Kalikaki, A. (2015)Caucasian (Greece)10790/1760 (37–78)IIIB-IVDDP/CBP-basedOR, OS, PFSPCR-RFLP ERCC1 rs3212986, XRCC1 rs25487 112 Zou, H. Z.…”
Section: Resultsmentioning
confidence: 99%
“…(2014)Asian (China)192132/6060.8 (26–79)IIIA-IVPlatinum-basedOR, OSMALDI-TOF-MS ERCC1 rs3212986 rs11615 rs2298881 105 Lv, H. (2014)Asian (China)9154/3759 (34–80)IIIB-IVDDP+TAX/GEM/NVPORTaqMan-MGB GSTP1 rs1695 106 Krawczyk, P. (2014)Caucasian (Poland)11559/5661 (NR)II-IVDDP/CBP+PEMOSHRM, PCR-RFLP ERCC1 rs11615 107 Sullivan, I. (2014)Caucasian (Spain)161125/3663.7 (36–85)IIIA-IVDDP/CBP-basedOR, OSDynamic array chips ERCC1 rs3212986 rs11615, XPD rs13181 rs1799793, XPG rs1047768 rs17655, XRCC1 rs25487 rs1799782, rs25489, XPA rs1800975 108 Dong, C M. (2014)Asian (China)9238/5457 (40–6)IIIB-IVPlatinum-basedORPCR-RFLP MTHFR rs1801133 109 Liu, D. (2014)Asian (China)378297/8162.4 (36–78)I-IVDDP+GEM/DOC/NVP/TAXOR, OSPCR-RFLP XPG rs1047768 rs17655 XRCC1 rs25487 rs1799782 110 Kou, G. (2014)Asian (China)5014/3656 (45–78)IIIB-IVDDP+NVPORPCR-RFLP ERCC1 rs3212986 111 Kalikaki, A. (2015)Caucasian (Greece)10790/1760 (37–78)IIIB-IVDDP/CBP-basedOR, OS, PFSPCR-RFLP ERCC1 rs3212986, XRCC1 rs25487 112 Zou, H. Z.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al suggested that Chinese Han people with rs1799782 TT/CT genotype of XRCC1 gene may have increased risk of developing colorectal cancer [8]. Some previous studies suggested that XRCC1 rs1799782 polymorphism was associated with the objective response rate (ORR) of platinum-based chemotherapy [9][10][11][12][13][14][15][16][17][18][19][20][21]. However, the results were not coincident.…”
Section: Introductionmentioning
confidence: 60%
“…The TT genotype in the ERCC5 rs1047768 polymorphism (T→C substitution at codon 46, exon 2, His→His) has been associated with increased ORR (OR=1.90; CI95%=1.10, 3.28; TT vs CC), OS (HR=0.52; CI95%=0.31, 0.96; TT vs CC) and PFS (HR=0.47; CI95%=0.22, 0.82; TT vs CC) [129]. A meta-analysis which included 5 studies with 846 cases, has recently confirmed these results for ORR (RR=1.23; CI95%=1.11, 1.36 I 2 =0%; Pheterogeneity=0.480; CT/TT vs CC) [102] while no association of rs1047768 with toxicity was found in 74 Spanish NSCLC patients [76].…”
Section: Ercc5mentioning
confidence: 99%